Autonomía eléctrica del campus "General Gillermo Rodriguez Lara" de la Universidad de las Fuerzas Armadas -ESPE- extensión Latacunga, en base a la eficiencia y eficacia de fuentes alternativas de emergencia. Propuesta de un sistema de energía eléctrica alternativa. - Mena Lasluisa, Pablo Orlando (2013)
With the purpose of setting up an emergency system that guarantees the electric autonomy in the “Guillermo Rodriguez Lara” campus of ESPE – Latacunga which is in its first phase of construction, a diagnostic of the electric demand is made by means of a field searching and through documental search in the Army Forces University – ESPE – Quito keeping in mind the similarity of infrastructure and institutional identity. The bibliographic revision gives evidence about the art of the works made with this purpose all around the world, in the country and in the local area. The methodology allowed defining the cost of failure, in the Cotopaxi province and the FMIK net and the TTIK net of the Cotopaxi Electrical enterprise as well as the technical features of the distribution feeders of the same company on the delivery node which is necessary to elucidate among the studied choices the most suitable one. With the similar electrical demand gotten of the campus a double feeding is analyzed in the local enterprise to 13.8 Kv, using diesel generation to the whole campus and for especial loads and direct current. Finally, in case of shorts it is proposed a continuous generation system composed by UPS and a diesel group.